Does a cooperative training design influence pre-service teachers’ perceived quality of life? - Legrain, Pascal; Lesellier, Jeremy; Sanchez-Larrea, Sophie; Escalie, Guillaume (Frontiers in Education, 2023)
Purpose: One of the main challenges of teacher education is to prepare pre-service teachers (PSTs) to implement various instructional models that promote the quality of learning at school. Beyond individualistic efforts and competition, cooperative learning (CL) environments provide PSTs with opportunities to experience positive interpersonal relationships and support. However, both instructional content knowledge acquisition and motivation for serenely implementing learning environments later in classrooms depend on PSTs being trained to make links between theory, research, and practice. The purpose of this study is to explore the effects of CL instructional programs on PSTs’ quality of life in light of their motivation and competencies for teaching in comparison with traditional direct instruction in the physical education (PE) setting. Method: After a pre-test, 69 PE-PSTs were randomly assigned to one of the following three training conditions comprising a theoretical presentation of CL designs coupled with (a) a Learning Jigsaw experience (LJE), (b) a Teaching Jigsaw experience focused on instructional acts (TJE), and (c) a Direct Instruction experience (DI). Results: Although integrating CL into the PE-PST training program positively influenced instructional content knowledge acquisition, unexpected results related to participants’ motivation were obtained when the instructor made links between theory, research, and practice focusing on the teaching activity during Jigsaw training sessions. Discussion: Recommendations for planning innovative conditions in PE-PSTs’ training with respect to CL instruction and quality of life are discussed.